2012
DOI: 10.1007/s00268-012-1805-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 10 % Sucralfate Ointment in the Reduction of Acute Postoperative Pain After Open Hemorrhoidectomy: A Prospective, Double‐Blind, Randomized, Placebo‐Controlled Trial

Abstract: Sucralfate ointment reduced the acute postoperative pain after hemorrhoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Ala S et al used topical metronidazole 10% in post hemorrhoidectomy patients that resulted in significantly reduced pain on day 07 and 14 ( p≤0.04 ) as compared to placebo. 6 Similar results obtained by Gonzalez A et al in 2015 where patients experienced significantly less post-operative pain. 5 Pourghassem J et al in 2012 studied 40 patients randomly distributed between topical metronidazole and placebo, showed that patients on topical metronidazole experienced less pain, they required few analgesics.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Ala S et al used topical metronidazole 10% in post hemorrhoidectomy patients that resulted in significantly reduced pain on day 07 and 14 ( p≤0.04 ) as compared to placebo. 6 Similar results obtained by Gonzalez A et al in 2015 where patients experienced significantly less post-operative pain. 5 Pourghassem J et al in 2012 studied 40 patients randomly distributed between topical metronidazole and placebo, showed that patients on topical metronidazole experienced less pain, they required few analgesics.…”
Section: Discussionsupporting
confidence: 76%
“… 3 Various remedies have been suggested to alleviate the post-operative pain like GTN 0.2%, topical NSAIDS, Ca channel blockers and metronidazole. 4 Studies show that metronidazole in both forms (topical and oral) significantly reduces the post-operative pain ( p0.004, p0.0011 ) 5 , 6 and improves the wound healing compared to placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been proposed: acupuncture [7], creams or gels with several agents (nitrites, anesthetics, calcium antagonists, sucralfate, metronidazole, salsobromoiodic, cholestyramine) for topical application [8], [9], [10], [11], [12], [13], [14], [15], nonsteroidal anti-inflammatory suppositories [11], local infiltration with botulinum toxin [16], or local anesthetic agents [5], [6], [17] or even ambulatory PCA (patient controlled analgesia) pumps [18].…”
Section: Discussionmentioning
confidence: 99%
“…13 In another work by Ala et al, topical sucralfate did decreased posthemorrhoidectomy pain in the first 24 h after surgery, by thorough revision of the methods and results of this study and Mirani study; we had found high cross matching between them which may raise doubts about plagiarism. 14 Sucralfate also had been tried in post anal fistulotomy wound and proved to be effective regarding pain control and wound healing. 15 Despite being inferior to sucralfate; local anesthetic lidocaine ointment did reduced pain intensity post hemorrhoidectomy when compared to placebo group.…”
Section: Discussionmentioning
confidence: 99%